Prevalence, comorbidity and factors associated with sleeping, crying and feeding problems at 1 month of age: A community‐based survey. (12th October 2018) - Cook, Fallon; Mensah, Fiona; Bayer, Jordana K; Hiscock, Harriet
Abstract : Aim: To examine, in a community cohort of healthy one‐month‐old infants, (i) the prevalence of early infant sleeping, crying and feeding problems; (ii) the extent to which they co‐exist; and (iii) infant and mother characteristics associated with each problem alone and with comorbid problems. Methods: A survey at 4 weeks of infant age examined the presence of infant sleeping, crying and feeding problems (yes/no); parenting self‐efficacy; rating of self as a tense person; and doubts about parenting at bedtime. Results: A total of 770 mothers (39% of those approached) with a total of 781 infants (11 twins) took part. Infant sleeping, crying and feeding problems were reported by 38.5, 27.4 and 25.2% of mothers, respectively. On comorbidity, 25.5% reported one problem, 20.5% reported two and 7.3% reported all three problems. Mothers of first‐born infants reported more crying problems and comorbid problems. Mothers who described themselves as a 'tense person' reported more infant feeding problems. Maternal doubt and low self‐efficacy were consistently associated with each type of infant problem and comorbid problems (adjusting for other factors). Conclusion: Mothers expressing doubt and low parenting self‐efficacy may benefit from additional support and guidance on normal infant behaviour.